2000
DOI: 10.1074/jbc.m006553200
|View full text |Cite
|
Sign up to set email alerts
|

p21-activated Kinase (PAK1) Is Phosphorylated and Activated by 3-Phosphoinositide-dependent Kinase-1 (PDK1)

Abstract: In this study, we show that phosphorylated 3-phosphoinositide-dependent kinase 1 (PDK1) phosphorylates p21-activated kinase 1 (PAK1) in the presence of sphingosine. We identify threonine 423, a conserved threonine in the activation loop of kinase subdomain VIII, as the PDK1 phosphorylation site on PAK1. Threonine 423 is a previously identified PAK1 autophosphorylation site that lies within a PAK consensus phosphorylation sequence. After pretreatment with phosphatases, autophosphorylation of PAK1 occurred at al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
185
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(188 citation statements)
references
References 53 publications
3
185
0
Order By: Relevance
“…Both Fra-1 and Runx2 are known downstream targets of the Wnt or cat/TCF signaling pathway (Mann et al, 1999;Dong et al, 2006). In this study, we found that insulin stimulates PAK-1 phosphorylation/activation in multiple cancer cell lines and in mouse intestinal tissues on Thr423, a target residue of phosphoinositide-dependent kinase isozyme-1, hence bypassing Akt (King et al, 2000). We have also found that PAK-1 knockdown significantly reduced insulin-stimulated c-Myc and cyclin D1 expression, as well as cell growth, and completely blocked the insulinstimulated interaction between b-cat and the c-Myc gene promoter.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Both Fra-1 and Runx2 are known downstream targets of the Wnt or cat/TCF signaling pathway (Mann et al, 1999;Dong et al, 2006). In this study, we found that insulin stimulates PAK-1 phosphorylation/activation in multiple cancer cell lines and in mouse intestinal tissues on Thr423, a target residue of phosphoinositide-dependent kinase isozyme-1, hence bypassing Akt (King et al, 2000). We have also found that PAK-1 knockdown significantly reduced insulin-stimulated c-Myc and cyclin D1 expression, as well as cell growth, and completely blocked the insulinstimulated interaction between b-cat and the c-Myc gene promoter.…”
Section: Discussionmentioning
confidence: 60%
“…PAK-1 was initially recognized as a downstream target of the Rho family GTPases, Rac1 and Cdc42, in regulating actin remodeling (Knaus and Bokoch, 1998;Zhou and Field, 2004;Arias-Romero and Chernoff, 2008). PAK-1 can also be activated by Akt (Zhou et al, 2003), or become directly phosphorylated/activated by PI3K (Tsakiridis et al, 1996) or phosphoinositide-dependent kinase isozyme-1 on Thr 423 (King et al, 2000), without requiring Akt. In this study, we show that insulin stimulates the phosphorylation/activation of PAK-1 in both intestinal cancer and non-cancer cell lines, and in several mouse tissues, including the intestines.…”
Section: Introductionmentioning
confidence: 99%
“…33 However, perifosine did not affect the levels of Ser 241 p-PDK-1, in agreement with the observations of others 17,34 (Figure 3a). As a further proof that perifosine does not negatively affect PDK-1 activity, the phosphorylation state of Thr 423 PAK-1, a downstream target of Perifosine-mediated cytotoxicity in AML V Papa et al PDK-1, 35 was analyzed. Consistently, the drug did not change the levels of Thr 423 p-PAK-1 (Figure 3a).…”
Section: Perifosine Negatively Affects Cell Survival and Induces Apopmentioning
confidence: 99%
“…The GEF integrates G i␤␥ and PIP 3 signals to activate Rac1, which couples directly to PAK2 and cell migration. PAKs including PAK2 are believed to become autophosphorylated on Thr and Ser residues upon activation, but an alternative phosphorylation mechanism by PDK1 has also been described (42). CSF-1 activates class I A PI3Ks and PAK2 by a mechanism that might involve Rho-GTPases other than Rac (not shown in the model).…”
Section: Pi3k␥-dependent and Pi3k-independent G I -Mediated Activatiomentioning
confidence: 99%
“…Active Rac GTP precipitated by PAK-PBD was separated on SDS-PAGE, transferred to nitrocellulose membrane, and blotted for pan-Rac, followed by ECL detection. Left lanes, the total signal detected using cytosol preloaded with Chemokine-induced PI3K␥-Rac-Pak Signaling 43276 loop of the kinase domain and is known to be required for activation (41)(42)(43). The phospho-PAK Thr antibody demonstrated that RANTES stimulation of macrophages for 10 and 30 s triggered phosphorylation of PAK2 Thr-402 , but less so in PI3K␥Ϫ/Ϫ BMDM (Fig.…”
Section: Rantes-induced Rac Activationmentioning
confidence: 99%